Social media use and value creation in the digital landscape: a dynamic capabilities perspective / Sharifah Ramiezah binti Wan Za'aba - Wan Za'aba, Sharifah Ramiezah (Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA Sarawak, 2022)
The way enterprises and customers engage and exchange value has changed as a result of digitalization. While increased digitalization provides benefits for businesses, it also poses substantial obstacles. Managers encounter complicated and fast changing markets, but lack the specialised knowledge required to comprehend these changes and cope with them.